Pelatihan aplikasi komputer santri MDQH (Ma’had Darul Qur’an wal-Hadits) Almajidiah Asy-Syafi’ah NWDI-Pancor - Taufik Akbar; Ahwan Ahmadi; Hadian Mandala Putra; M Nuzuluddin; Intan Komala Dewi Patwari; Alimudin Alimudin (Universitas Hamzanwadi, 2023)
In public perception, religious scholars (Ulama) serve as highly trusted sources of information, particularly within Indonesian society. Therefore, it is imperative to ensure that Ulama possesses adequate digital literacy to convey accurate and reliable information. This study aims to provide computer training to the students (santri) of Ma'had MQDH NW Pancor, enabling them to master relevant computer technologies and applications. The training primarily focuses on internet literacy and Microsoft Office applications, employing a combination of lectures and hands-on practice. Ten participants from various levels of study were involved in the program, which took place at Laboratory 1, Faculty of Engineering, Hamzanwadi University. The results of the training revealed that 57.1% of the participants expressed high satisfaction levels, while 71.4% reported an increase in their understanding after completing the training. In conclusion, this computer training program has demonstrated positive benefits in enhancing the digital comprehension and skills of the students, preparing them to tackle digital challenges in the future.